Combinatory approaches prevent preterm birth profoundly exacerbated by gene-environment interactions - Cha, Jeeyeon (American Society for Clinical Investigation, 2013)
There are currently more than 15 million preterm births each year. We propose that gene-environment interaction is a major contributor to preterm birth. To address this experimentally, we generated a mouse model with uterine deletion of Trp53, which exhibits approximately 50% incidence of spontaneous preterm birth due to premature decidual senescence with increased mTORC1 activity and COX2 signaling. Here we provide evidence that this predisposition provoked preterm birth in 100% of females exposed to a mild inflammatory insult with LPS, revealing the high significance of gene-environment interactions in preterm birth. More intriguingly, preterm birth was rescued in LPS-treated Trp53-deficient mice when they were treated with a combination of rapamycin (mTORC1 inhibitor) and progesterone (P(4)), without adverse effects on maternal or fetal health. These results provide evidence for the cooperative contributions of two sites of action (decidua and ovary) toward preterm birth. Moreover, a similar signature of decidual senescence with increased mTORC1 and COX2 signaling was observed in women undergoing preterm birth. Collectively, our findings show that superimposition of inflammation on genetic predisposition results in high incidence of preterm birth and suggest that combined treatment with low doses of rapamycin and P(4) may help reduce the incidence of preterm birth in high-risk women.